HUBUNGAN ANTARA PERILAKU MAKAN ANAK DENGAN PERILAKU ORANG TUA DALAM PEMBERIAN MAKAN PADA TODDLER DI SLEMAN YOGYAKARTA - , YULANTICHA DIAZ AHWALIA AZIZA, Lely Lusmilasari, S.Kp., M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Children at toddler period cannot be fully independent in meeting their eating need. They can be very picky with foods and even be fussy eaters. Parents usually follow along with their children. Objective: To identify correlation between childrenâs eating behavior and parentsâ behavior in feeding toddlers. Method: The study was quantitative observational with analytic correlation method and cross sectional design. Samples of the study consisted of 85 respondents selected through simple random and total sampling technique. Subject included parents having children of 1-3 years old at the working area of Depok III Health Center Sleman Yogyakarta. The study used questionnaire of childrenâs eating behavior and parentsâ behavior in feeding their children. Statistical analysis used Pearson product moment correlation. Result: Score of r was 0.008 and p was 0.285